2009
DOI: 10.1093/europace/eun382
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of transvenous coil electrodes as single element subcutaneous array leads

Abstract: For implantable cardioverter defibrillator a 10 J safety margin between the defibrillation threshold (DFT) and the maximum output of the device is intended. In complex cases, the additional placement of a subcutaneous array lead is a common strategy for lowering the DFT. We report the successful use of transvenous coil electrodes as single element subcutaneous array leads in order to lower the DFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These leads are usually implanted subcutaneously, from the lower margin of the ICD pocket along the chest wall, and were reported to give a mean DFT reduction of 20% to 60%. [9][10][11] Juchem et al 16 reported two cases of transvenous coil lead being placed as a subcutaneous array electrode. There is no difference in implantation technique, but the coil portion of the transvenous leads is smaller (8 cm vs 25 cm length) than the coil of an array electrode and is therefore easier to position correctly.…”
Section: Discussionmentioning
confidence: 99%
“…These leads are usually implanted subcutaneously, from the lower margin of the ICD pocket along the chest wall, and were reported to give a mean DFT reduction of 20% to 60%. [9][10][11] Juchem et al 16 reported two cases of transvenous coil lead being placed as a subcutaneous array electrode. There is no difference in implantation technique, but the coil portion of the transvenous leads is smaller (8 cm vs 25 cm length) than the coil of an array electrode and is therefore easier to position correctly.…”
Section: Discussionmentioning
confidence: 99%